Влияния типа реактора на структурные особенности никелида титана, полученного методом СВС в атмосфере аргона - Мамазакиров, Ойбек Рустамович (Перспективы развития фундаментальных наук. Т. 1 : сборник научных трудов XIX Международной конференции студентов, аспирантов и молодых ученых, 26-29 апреля 2022 г.)
A study of the structural features of porous titanium nickelide based alloys obtained by the SHS method in the open and closed reactors in an argon atmosphere has been carried out. It was found that the sample obtained in a closed reactor had a larger average pore size than the sample synthesized in an open reactor. The reasons for that are explained by the fact that in a closed reactor the inert gas enters the reactor, heats up, receiving heat from the heater and mixing with the hot reaction gases. All heat is stored in the reactor and causes coalescence of small pores combining them into larger ones. And during synthesis in an open reactor, the gas transfers heat from the heater to the charge and removes heat from the sample. Moreover, the phase composition and parameters of the macro structure of the pore space ofTiNi alloys (porosity coefficients, average size of pores and interpore bridges) were determined.